Impact of severe mitral regurgitation on postoperative outcome after durable left‐ventricular assist device implantation. Issue 5 (31st December 2021) - Zubarevich, Alina; Szczechowicz, Marcin; Arjomandi Rad, Arian; Osswald, Anja; Papathanasiou, Maria; Luedike, Peter; Koch, Achim; Pizanis, Nikolaus; Kamler, Markus; Schmack, Bastian; Ruhparwar, Arjang; Weymann, Alexander
Abstract: Background: Mitral valve regurgitation (MR) is a common finding in patients with end‐stage heart failure. The aim of the study was to analyze the impact of preoperative moderate‐to‐severe MR on postoperative outcomes and survival after durable left‐ventricular assist device (LVAD) implantation. Methods: From August 2010 to May 2021, 246 patients underwent a durable LVAD implantation. We stratified the patients into two groups: Group A ( n  = 109) presented with MR 0‐I°, and Group B presented with MR II‐III° ( n  = 137). MR II‐III° was defined according to the current recommendations (i.e., vena contracta ≥ 7 mm, regurgitation volume ≥ 30 ml or effective regurgitation orifice area ≥ 20 mm 2 ). Results: Significantly more patients in Group B suffered from pulmonary hypertension and presented with chronic obstructive lung disease. We observed significantly higher rates of tricuspid regurgitation (TR) II‐III° in Group B (76.1%) versus Group A (14.8%) ( p  < 0.001) and TR III° in Group B (30.4%) versus Group A (3.7%) ( p  < 0.001). There was no difference in the incidence of right heart failure between the groups. Within our cohort, the in‐hospital, 1‐year, 3‐year, and 5‐year mortality was 22.4%, 32.1%, 50.7%, and 64.4%, respectively. Group B showed significantly worse overall survival ( p  = 0.05). Patients with preoperative TR II‐III° had a significantly worse survival than those with TR 0‐I° ( p  = 0.048). In patients presenting with MR II‐III°, we discovered that TR III° seems to predict both in‐hospital and mid‐term mortality. Conclusion: MR II‐III° negatively affects the outcomes in patients requiring LVAD implantation. Persisting MR II‐III° is an independent predictor of mortality. Patients with concomitant preoperative TR II‐III° are at increased risk of developing postoperative major adverse events. Addressing the MR might be considered for these patients. Abstract : Overall survival after durable left‐ventricular assist device implantation. Single center experience.